The Role of Customer Engagement as Mediation and Deal Proneness as Moderation - Retnosari, Marda Cahyanti; Nadlifatin, Reny (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Generation Z is a challenge and an opportunity for new businesses, considering that despite the high consumption rate, marketers often have difficulty influencing them. This study analyzes the influence of trust, flow experience, and perceived value on purchase intention, with customer engagement as mediation and deal proneness as moderation. This study uses a quantitative approach involving 402 Generation Z respondents actively using TikTok live-streaming e-commerce in Jakarta. Data was collected through a questionnaire which was then analyzed using partial least square path modeling (PLS-SEM). The findings show that trust in community members, trust in the broadcaster, trust in the platform, perceived value, and flow experience have a significant positive effect on customer engagement, while trust in the product has no significant effect. In addition, trust in community members, trust in the broadcaster, trust in the product, perceived value, and flow experience had a significant positive effect on purchase intention, while trust in the platform had no significant effect. Customer engagement partially mediates the influence of trust, perceived value, and flow experience on purchase intention, while deal proneness strengthens the influence of customer engagement on purchase intention. The managerial implications of these findings include developing marketing approaches that improve the quality of live-streaming interactions, building strong communities, leveraging trusted influencers, highlighting product value, and leveraging promotions to capture the attention of Generation Z. Marketers can design more relevant and relevant live-streaming experiences, creating a more dynamic and consumer-oriented e-commerce ecosystem to increase sales.